Search of the Molding Form Connector Plane on the Approximation Basis By the Many-Sided Surface With Use of the Convex Sets Theory - Matarneh, Rami; Sotnik, S.; Lyashenko, V. (TJPRC Pvt. Ltd., 2018)
Use of plastic as material for production of different products – one of the priority directions of the current technologies in construction and the industry. The important aspect of such technology, processes should be considered as high-quality production of molding forms for the subsequent production of plastic products. It allows to unify production of difficult products, to increase optimality procedures of their production, reliability and quality of the received products. The general ideology of the search for the molding form connector plane is revealed by means of an approximation with a many-sided surface. The technique of searching for the connector plane molding form using the theory of convex sets has been developed. The generalized technique for searching of the molding form connector plane of plastic products on the basis of approximation of a many-sided surface with the use of the theory of convex sets is offered. The possibility of application of this technique for the solution of a task of increasing the accuracy of linear and circular interpolation of a movement trajectory of the tool cutting edge on the processing center is shown.
Keywords: Molding form; Approximation